PENERAPAN STRATEGI SQ4R UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR LARUTAN PENYANGGA BAGI PESERTA DIDIK KELAS XI IPA-1 SMA NEGERI 1 CEPIRING SEMESTER 2 TAHUN PELAJARAN 2015/2016 - Aris Gunawan (Majalah Ilmiah Inspiratif, 2016)
This research was motivated by the perceived problems of the chemistry learning less attractive for the learners, it is visible from a lack of motivation and curiosity to understand the issues related to the chemistry lesson. This is proved by analysis of daily tests in January 2016 obtained data from 35 learners only 9 (25.71%) students who reach KKM (75). The purpose of this research is to improve the activity and learning outcomes of the buffer solution through the implementation of strategies SQ4R for students of class XI IPA 1 SMA Negeri 1 Cepiring Semester 2 Academic Year 2015/2016.The method used in this research is classroom action research (CAR), using the model of action research Kemmis McTaggart consisting of four stages: planning, implementation, observation and reflection. The fourth stage of the research was conducted in two cycles.The results show that through the application of learning strategies SQ4R can increase the activity and learning outcomes of the buffer solution for students of class XI IPA 1 SMA Negeri 1 Cepiring Semester 2 Academic Year 2015/2016, the increased activity of learners at 66.29%, and the increased of cognitive aspects of learning outcome are 38.27%, affective aspects are 32.00%, as well as psychomotor aspects are 24.56%. Keywords: Strategy SQ4R, Learning Activities, Learning Outcomes